Carbon–carbon triple bond‐containing materials for photo(electro)catalytic solar hydrogen production - Wenyan Li; Yang Lu; Yawen Tang; Hanjun Sun (Carbon Energy)
Abstract The use of solar energy to produce hydrogen has been one of the research hotspots in recent years. With the continuous exploitation of solar hydrogen evolution, the performance of photo(electro)catalysts has been greatly optimized. However, the solar‐driven hydrogen production for most semiconductors, especially for organic semiconductors, is limited due to the lack of active centers and serious electron–hole recombination. Recently, it has been reported that carbon‐carbon triple bonds (C≡C) can function as active sites for hydrogen evolution, and diacetylenic moiety in organic semiconductors is able to increase carrier migration as well. Therefore, organic semiconductors containing C≡C have attracted considerable attention in the past few years. In this review, organic materials or organic–inorganic hybrids containing C≡C for photo(electro)catalytic solar hydrogen production are classified first, including graphdiyne, conjugated acetylene polymers, some covalent organic frameworks, and metal–organic frameworks. After that, the structure, properties, and advantages and disadvantages of C≡C‐containing materials are introduced and summarized. Apart from these, this review also presents advances in materials containing C≡C in the field of solar hydrogen generation. Finally, perspectives on the future development of C≡C‐containing materials in the field of solar hydrogen generation are also briefly anticipated. This review provides pertinent insights into the main challenges and potential advances in the organic semiconductors for solar‐driven hydrogen production, which will also greatly contribute to other photo(electro)catalytic reactions.